Analysis of Polyvinylidene Fluoride (PVDF) and Polyethersulfone (PES) Ultrafiltration Membranes Incorporated with Graphene Oxide (GO) Performance for Textile Wastewater Treatment - Arman, Muhamad Amirul Haziq; Misdan, Nurasyikin (Progress in Engineering Application and Technology, 2023)
The application of membrane technology to remove pollutant dyes in the textile industry is a significant development today. The modification of membranes to improve their properties has been shown to improve the permeation flux and dye rejection efficiency of the composite ultrafiltration membrane. Therefore, in this experiment, graphene oxide was used as an additive to modify the polyethersulfone (PES) and polyvinylidene fluoride (PVDF) membranes and prepare mixed matrix membranes (MMM). Three different ratios were used to fabricate the membrane which are 1:1, 2:1, and 1:2 of NMP and PVDF. For each ratio will be added graphene oxide to see the performance through the rejection. This research is dedicated to using methylene blue as feed dye (50ppm) to study the effect of the composite ultrafiltration membrane performance. The characterization of the membrane was studied using the AFM, SEM, FTIR, contact angle, permeation flux, and dye rejection by investigating the influence of PVDF-PES and GO structure. The performance of the ultrafiltration membranes displayed a lower dye rejection which is lower than 10%. The membranes don’t show high improvement with the addition of 1g graphene oxide. Therefore, the composite ultrafiltration membrane does not achieve the expectation for dye rejection.